Modelling Empty Container Repositioning Logistics - Song, Dong-Ping.; Dong, Jingxin (Cham : Springer International Publishing : Imprint: Springer, 2022)
The book takes the inventory control perspective to tackle empty container repositioning logistics problems in regional transportation systems by explicitly considering the features such as demand imbalance over space, dynamic operations over time, uncertainty in demand and transport, and container leasing phenomenon. The book has the following unique features. First, it provides a discussion of broad empty equipment logistics including empty freight vehicle redistribution, empty passenger vehicle redistribution, empty bike repositioning, empty container chassis repositioning, and empty container repositioning (ECR) problems. The similarity and unique characteristics of ECR compared to other empty equipment repositioning problems are explained. Second, we adopt the stochastic dynamic programming approach to tackle the ECR problems, which offers an algorithmic strategy to characterize the optimal policy and captures the sequential decision-making phenomenon in anticipation of uncertainties over time and space. Third, we are able to establish closed-form solutions and structural properties of the optimal ECR policies in relatively simple transportation systems. Such properties can then be utilized to construct threshold-type ECR policies for more complicated transportation systems. In fact, the threshold-type ECR policies resemble the well-known (s, S) and (s, Q) policies in inventory control theory. These policies have the advantages of being decentralized, easy to understand, easy to operate, quick response to random events, and minimal on-line computation and communication. Fourth, several sophisticated optimization techniques such as approximate dynamic programming, simulation-based meta-heuristics, stochastic approximation, perturbation analysis, and ordinal optimization methods are introduced to solve the complex stochastic optimization problems. The book will be of interest to researchers and professionals in logistics, transport, supply chain, and operations research.
Part I -- Chapter 1. Container logistics chain and empty container repositioning (ECR) -- Part II -- Chapter 2. Closed-form optimal ECR policy in a single depot with random demand -- Chapter 3. Optimal ECR policy in two-depot stochastic systems: periodic-review -- Chapter 4. Optimal ECR policy in two-depot stochastic systems: continuous-review -- Chapter 5. Optimal and near-optimal ECR policies in hub-and-spoke stochastic systems -- Chapter 6. Container sharing and ECR in two-depot stochastic systems -- Chapter 7. Optimal ECR in general inland transport systems with uncertainty -- Part III -- Chapter 8. Container fleet sizing and ECR in shipping route with uncertain demands -- Chapter 9. Container fleet sizing and ECR in shipping service considering inland transport times with uncertainty -- Chapter 10. Container lease term optimisation and ECR in shipping route with uncertain demand -- Chapter 11. Evaluate flexible destination port ECR policy in shipping route with uncertain demand -- Chapter 12. Laden container routing and ECR in shipping network with multiple service routes -- Chapter 13. Discrete-event driven simulation model for laden container distribution and ECR in shipping network -- Chapter 14. Evaluate ECR policies in liner shipping systems using simulation model -- Chapter 15. Conclusions.
Keywords: Business logistics; Industrial Management; Operations research; Management science; Logistics; Industrial Management; Supply Chain Management; Operations Research and Decision Theory; Operations Research, Management Science .